Pelayanan Pencegahan dan Penyembuhan Penyakit di Gereja Sebelum dan Selama Pandemi Covid-19 - Sony Kristiantoro (Sekolah Tinggi Teologi Berita Hidup, 2023)
So far, one form of service that is usually carried out by the Pentecostal-Charismatic Church (GP-K) is the Healing Ministry, although it still feels a bit foreign to the Mainstream Church (GM). Between the two, there are still quite sharp differences in understanding and practice, which often lead to serious problems. This was seen before and during the Covid-19 pandemic that hit Indonesia. The author will describe a comparison of understanding and practice that occurs in terms of healing services in between the two churches. In addition to conflicts that surfaced, through the Covid-19 Pandemic, churches were also taught to carry out a more complete and integrative type of service in the context of preventing and curing infectious diseases such as Covid-19. So far, in churches, this type of service in the health sector in the form of prevention and healing has not yet become a complete form of service and has not been well integrated. The church can make a good and planned Preventive Service, create or develop a responsible healing theology, form a Team and empower the talents of all members of the congregation to be involved, and how the church becomes a healing community. These things are believed to be an effective means for witnessing and strengthening each other among the congregation during the Covid-19 Pandemic and beyond.ABSTRAKSelama ini satu bentuk pelayanan yang biasa dilakukan oleh Gereja Pentakostal-Kharismatik (GP-K) adalah Pelayanan Penyembuhan (Healing Ministry), walaupun masih agak terasa asing bagi Gereja Mainstream (GM). Di antara keduanya, masih terjadi perbedaan pemahaman dan praktik yang cukup tajam, yang tidak jarang menimbulkan persoalan serius. Hal ini nampak sebelum dan saat Pandemi Covid-19 melanda Indonesia. Penulis memaparkan perbandingan pemahaman dan praktik yang terjadi dalam hal pelayanan penyembuhan di di antara kedua gereja. Selain pertentangan yang muncul ke permukaan, melalui Pandemi Covid-19, gereja juga diajar untuk melakukan jenis pelayanan yang lebih utuh dan integratif dalam rangka pencegahan dan penyembuhan penyakit menular seperti Covid-19 ini. Selama ini di gereja-gereja, jenis pelayanan dalam bidang kesehatan berupa pencegahan dan penyembuhan ini belum menjadi sebuah bentuk pelayanan yang utuh dan belum terintegrasi secara baik. Gereja bisa membuat Pelayanan Pencegahan yang baik dan terencana, membuat atau menyusun teologi penyembuhan yang bertanggungjawab, membentuk Tim dan memberdayakan talenta semua warga jemaat untuk terlibat, dan bagaimana gereja menjadi komunitas penyembuh. Hal-hal tersebut diyakini bisa menjadi sarana efektif bagi kesaksian dan saling menguatkan di antara jemaat pada masa Pandemi Covid-19 dan sesudahnya.